2020
DOI: 10.1002/chem.202001796
|View full text |Cite
|
Sign up to set email alerts
|

Thiophene and Selenophene Binding at a Pd3 Cluster Site

Abstract: We report the triply bridging coordination of thiophene and selenophene to a trinuclear metal cluster site. The triply bridging coordination of selenophene at a Pd3 site forms a unique spiro‐type Pd5 cluster. Furthermore, either thiophene or selenophene is accommodated stably at a Pd3 site supported by a backside μ3‐cyclooctatetraene ligand through the face‐capping μ3‐coordination. The Pd3 site supported by the cyclooctatetraene ligand showed higher binding affinity of benzene over thiophene, although a Pd2 si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 68 publications
0
2
0
Order By: Relevance
“…47 Yamamoto et al reported synthesis of a sandwich complex with asymmetric coordination of thiophene and selenophene at a Pd3 cluster site. 48 Formation of alloyed tetranuclear asymmetric metal chain, Pd4-nPtn (n = 0-3), supported by tetraphosphine containing a P-N-P phosphazane bridge, rac-bis[(diphenylphosphinomethyl)phenylphosphino]phenylamine, was demonstrated by Tanase, Nakajima, and co-workers. 49 For recognition of hydrogen phosphonate anions, Nakamura et al newly synthesized per(5-N-carboxamide-5-dehydroxylmethyl)-β-cyclodextrins.…”
Section: Introductionmentioning
confidence: 99%
“…47 Yamamoto et al reported synthesis of a sandwich complex with asymmetric coordination of thiophene and selenophene at a Pd3 cluster site. 48 Formation of alloyed tetranuclear asymmetric metal chain, Pd4-nPtn (n = 0-3), supported by tetraphosphine containing a P-N-P phosphazane bridge, rac-bis[(diphenylphosphinomethyl)phenylphosphino]phenylamine, was demonstrated by Tanase, Nakajima, and co-workers. 49 For recognition of hydrogen phosphonate anions, Nakamura et al newly synthesized per(5-N-carboxamide-5-dehydroxylmethyl)-β-cyclodextrins.…”
Section: Introductionmentioning
confidence: 99%
“…Selenophene derivatives have also been used as ligands in coordination chemistry [91][92][93][94][95][96][97]. After a pre-activation with a halide or an organometallic (B, Li, Mg, Sn or Zn), these compounds can be employed as reagents in the formation of new C-C [98][99][100][101][102][103][104][105][106][107], C-N [108][109][110] and C-S [111] bonds under Pd or Cu catalysis, through Heck, Stille, Negish, Kumada, Suzuki and Sonogashira coupling reactions.…”
Section: Introductionmentioning
confidence: 99%